2022
DOI: 10.1186/s13071-022-05340-5
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the jejunal microbiota and fecal metabolite profiles of rabbits infected with Eimeria intestinalis

Abstract: Background Rabbit coccidiosis is a major disease caused by various Eimeria species and causes enormous economic losses to the rabbit industry. Coccidia infection has a wide impact on the gut microbiota and intestinal biochemical equilibrium. In the present study, we established a model of Eimeria intestinalis infection in rabbits to evaluate the jejunal microbiota and fecal metabolite profiles. Methods Rabbits in the infected group were orally inoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…The consequent intestinal damage and microbiota disturbance lead to increased host vulnerability to enteritis, as manifested by DSS-induced inflammatory bowel diseases. We utilized E. hellem and E. intestinalis , two commonly diagnosed digestive tract-infecting microsporidia species with comparable endemic rates, in our study to get a comprehensive view of the effects of microsporidia on epithelium barriers ( 29 , 30 ). Our findings may help to explain the recurrent diarrheal and other intestinal abnormalities after microsporidia infection on molecular basis.…”
Section: Discussionmentioning
confidence: 99%
“…The consequent intestinal damage and microbiota disturbance lead to increased host vulnerability to enteritis, as manifested by DSS-induced inflammatory bowel diseases. We utilized E. hellem and E. intestinalis , two commonly diagnosed digestive tract-infecting microsporidia species with comparable endemic rates, in our study to get a comprehensive view of the effects of microsporidia on epithelium barriers ( 29 , 30 ). Our findings may help to explain the recurrent diarrheal and other intestinal abnormalities after microsporidia infection on molecular basis.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular immune responses play a dominant role in immunity against coccidiosis ( Chapman, 2014 ). Eimeria infection in rabbits damages the jejunal structure, and increases intestinal inflammation, and disrupts gut microbiota and metabolic homoeostasis ( Yuan et al., 2022 ). Altered faecal microbiota and metabolites are potential biomarkers of coccidiosis infestation ( Yuan et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eimeria infection in rabbits damages the jejunal structure, and increases intestinal inflammation, and disrupts gut microbiota and metabolic homoeostasis ( Yuan et al., 2022 ). Altered faecal microbiota and metabolites are potential biomarkers of coccidiosis infestation ( Yuan et al., 2022 ). In this study, the cellular immune responses induced by Eimeria magna and Eimeria media in the presence of Moringa oleifera and Vernonia amygdalina leaves extracts were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…It has shown that humoral immunity is crucial for combating coccidial infections (Constantinoiu et al 2008 ; Yuan et al 2022 ; Ding et al 2004 ; Zhao et al 2021a , b ). Serum IgG levels in the immunized rEmMIC2 and rEmMIC3 protein groups were significantly higher than those in the control group, confirming that rEmMIC2 and rEmMIC3 proteins induced humoral immunity.…”
Section: Discussionmentioning
confidence: 99%